PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI WEBSITE UNTUK MENINGKATKAN PROMOSI DI ZARIND WATERBOOM - Faizah, Putri Alya Nur; Sujadi, Harun (Universitas Majalengka, 2025)
The rapid development of digital technology has brought significant changes to tourism promotion strategies, with websites becoming one of the most effective media for delivering information quickly, accurately, and in a well-structured manner. Zarind Waterboom, a water tourism destination in Majalengka Regency, still faces challenges in its promotional efforts due to limited media usage and a lack of informative content. This study aims to design and implement a website-based information system to improve information accessibility and enhance visitor interest. The research methodology includes literature review, needs analysis, system design using the waterfall approach, and website implementation with HTML, CSS, and PHP. The results indicate that the developed website successfully provides key information such as ticket prices, facilities, location photos, and an interactive map to help visitors easily find the destination. The presence of this website enables the management to expand its promotional reach, improve interaction with potential visitors, and strengthen its digital marketing strategy. This research is expected to serve as a practical solution for Zarind Waterboom’s management in optimizing tourism promotion and attracting more visitors.